Electrospun Nanofibers from Recycled Styrofoam: Characterization and Smoke Filtration Performance for Environmental Sustainability - Rajak, Abdul; Tarigan, Chalpin Sapenta (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2025)
Cigarette smoke pollution contains PM₂.₅ particles with sizes ranging from 0.1 to 2.5 µm, along with nicotine and tar, while conventional filters have limited effectiveness in capturing ultrafine pollutants. The increasing use of Styrofoam in various industries has contributed to environmental challenges due to its resistance to natural degradation and limited recycling. This study develops an electrospun nanofiber-based cigarette smoke filter from recycled Styrofoam by optimizing electrospinning parameters to achieve controlled fiber morphology and enhanced filtration. Optimized parameters—including applied voltage, flow rate, needle-to-collector distance, viscosity, and solution concentration—enabled the fabrication of nanofibers with uniform morphology. SEM characterization revealed fiber diameters ranging from 0.88 to 2.23 µm, with a basic weight of 0.005–0.009 g/cm², thickness of 0.007–0.016 cm, and porosity of 61–76%. Filtration tests demonstrated PM₂.₅ capture, with visible tar deposition turning the nanofibers yellow-brown. Nanofiber mass increased post-filtration, correlating with contact time variation. Post-filtration FTIR analysis revealed peak shifts at 3377–3413 cm⁻¹ (OH stretching) and 1447 cm⁻¹ (NH bending), indicating nicotine and tar adsorption. These findings demonstrate that electrospun styrofoam-derived nanofiber membranes provide an effective alternative for cigarette smoke filtration, offering high efficiency and a sustainable approach to plastic waste reduction